WATER ECOSYSTEM SERVICES AND THE BOTTLENECKS IN THEIR IMPLEMENTATION FOR DRINKING WATER MANAGEMENT: A STUDY IN THE SAN MARTIN REGION, PERUVIAN AMAZON. - NORIEGA-MURRIETA, Javier (2024)
Understanding and managing Water Ecosystem Services (WES) are fundamental to the sustainability of ecosystem-rich regions. To understand the relationship between water ecosystem services and the challenges of implementing conservation projects in drinking water management in San Martín, in the Peruvian Amazon, a survey was conducted with 52 key stakeholders in the drinking water sector, ranging from those responsible for Municipal Technical Areas to those working in supplier companies. Structured questionnaires were designed, reviewed, and validated, ensuring that the questions were clear and useful. Data analysis employed statistical methods such as Gamma association and Somers' D test, which helped identify important connections related to more responsible and sustainable water management. The results show a strong correlation between water ecosystem services and bottlenecks, with legal, institutional, social, technical, economic, and political factors significantly influencing management. The findings underscore the need for strong legal frameworks, appropriate policies, community participation, and technical expertise to improve sustainability. Therefore, drinking water management in San Martín requires a multidimensional approach that integrates legal, institutional, social, economic, and technical aspects, ensuring the provision of drinking water and the conservation of ecosystems in this biodiverse region.